2007
DOI: 10.1148/radiol.2432051714
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Damage in Alzheimer Disease and Mild Cognitive Impairment: Assessment with Diffusion-Tensor MR Imaging and Parallel Imaging Techniques

Abstract: Reduced FA and RA values in patients with AD suggest that diffusion-tensor imaging of the brain can be used to confirm clinical manifestation of AD but is less applicable in the detection of MCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
150
4
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(180 citation statements)
references
References 32 publications
24
150
4
2
Order By: Relevance
“…As a major risk factor for dementia, diabetes is reported to be closely associated with the pathological processes of various dementias such as AD and frontotemporal dementia (FTD). AD can be regarded as a cortical disconnection syndrome that affects not only the cortical neurons but also the axons and dendrites in the cerebral WM (18). MCI, the prodromal phase of AD, impairs memory function and disrupts widespread WM tracts (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a major risk factor for dementia, diabetes is reported to be closely associated with the pathological processes of various dementias such as AD and frontotemporal dementia (FTD). AD can be regarded as a cortical disconnection syndrome that affects not only the cortical neurons but also the axons and dendrites in the cerebral WM (18). MCI, the prodromal phase of AD, impairs memory function and disrupts widespread WM tracts (19).…”
Section: Discussionmentioning
confidence: 99%
“…Fractional anisotropy (FA) and mean diffusivity (MD) describe fiber density, axonal diameter, and myelination in WM based on quantitative measure of the degree of diffusion anisotropy (15,16). As reported previously based on the DTI technique, decreased FA or increased MD in varieties of cognitive dysfunction related to Alzheimer disease (AD) (17,18), amnestic mild cognitive impairment (MCI) (19), schizophrenia (20,21), and type 1 diabetes (22), etc. Thus, DTI techniques are important for exploring more sensitive imaging-based biomarkers in prevention and early treatment of cognitive dysfunction induced by T2DM.…”
mentioning
confidence: 92%
“…It is very difficult to summarize the general picture of these results because other studies on AD "all stages" [23,37,40,75] reported no significant differences in MD or FA in the anterior and posterior CC when the patient group was compared with HC. Stahl and coworkers [40] also measured ADC and relative anisotropy and found no differences between AD patients and HC. Furthermore, the findings of studies on more homogeneous patients, such as those with mild AD, are discrepant.…”
Section: Diffusion-weighted Imaging and Diffusion Tensor Imaging Studiesmentioning
confidence: 95%
“…At present, the DTI study results on MCI patients can be divided into two groups: 1) DTI studies on both amnesic and MCI "all subtypes" [23,40,41,84,85,88] that found no differences in MD and/or in FA in the CC compared with HC; and 2) the most recent studies [83,86,[89][90][91], which reported differences. One study on MCI "all subtypes" [89] found a significant change in MD and FA in the genu and the splenium of the CC in patients compared with HC.…”
Section: Diffusion-weighted Imaging and Diffusion Tensor Imaging Studiesmentioning
confidence: 99%
See 1 more Smart Citation